Digital tools and welfare: adoption determinants among ginger producers in Southern and Central Ethiopia - Gizachew, Fetagn; Kuma, Berhanu; Tafesse, Alula; Lambamo, Alemu (Frontiers in Sustainable Food Systems, 2024)
This study investigated the role of digital tools in agricultural extension services among smallholder ginger producers in Southern and Central Ethiopia, addressing the persistent challenge of low adoption rates despite their recognized benefits. Using a mixed-methods approach, the research identified the socio-economic, institutional, and technological factors influencing farmers' adoption decisions. The analysis, based on an Endogenous Switching Regression model, highlighted the significant effects of digital tool adoption on both agricultural productivity and household income. The findings emphasized the need for targeted policies to promote digital tool uptake, particularly through investments in digital infrastructure, expanded access to ICTs, and the development of tailored extension services. Such efforts are critical to enhancing rural livelihoods, promoting sustainable agricultural practices, and fostering economic stability in the region.